2006
DOI: 10.1097/01.ccm.0000206105.05626.15
|View full text |Cite
|
Sign up to set email alerts
|

Critical care delivery in the United States: Distribution of services and compliance with Leapfrog recommendations*

Abstract: ICU services are widely distributed but heterogeneously organized in the United States. Although high-intensity ICUs have been associated previously with improved outcomes, they were infrequent in our study, especially in smaller hospitals, and virtually no ICU met the Leapfrog standards before their dissemination. These findings highlight the considerable challenge to any efforts designed to promote either 24-hr physician coverage or high-intensity model organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
286
2
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(296 citation statements)
references
References 34 publications
6
286
2
2
Order By: Relevance
“…This finding is consistent with evidence from the United States, where it has been demonstrated that less than half of the ICUs had coverage by an intensivist or a dedicated physician. 17 However, before determining the projected workforce needed to staff an expanded number of critical care beds, problems with intensivist shortages, physician burnout, and rising physician costs may lead to further difficulties in the appropriate staffing of current ICUs that lack intensivists. 18,19 Some issues regarding rising physician costs may be mitigated by the potential health care savings generated by intensivist staffing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is consistent with evidence from the United States, where it has been demonstrated that less than half of the ICUs had coverage by an intensivist or a dedicated physician. 17 However, before determining the projected workforce needed to staff an expanded number of critical care beds, problems with intensivist shortages, physician burnout, and rising physician costs may lead to further difficulties in the appropriate staffing of current ICUs that lack intensivists. 18,19 Some issues regarding rising physician costs may be mitigated by the potential health care savings generated by intensivist staffing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while the data may be specific to Ontario, it is consistent with other reports that highlight the need for significant planning for the delivery of critical care services. 3,8 In conclusion, the combination of an aging population and inefficiencies in the management of critical care services will not only be a major challenge to the delivery of critical care over the coming years, but will also have a major impact on patients and their health care providers. It is evident that a rather dramatic fiscal investment in the critical care environment will be needed, together with a significant increase in the number of health care workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, our data are derived from Medicare for a single year, and thus we cannot evaluate whether transfer patterns are different for nonMedicare patients or how they might change over time. However, over half of ICU patients are elderly, (41) and Medicare is a domain of public policy interest in its own right. Second, our data reflect transfers between critical care hospitalizations; limitations in the data prevent us from examining only direct ICU-to-ICU transfers.…”
Section: Discussionmentioning
confidence: 99%